2020
DOI: 10.1002/acp.3639
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of generating questions, testing, and restudying on students' long‐term recall in university learning

Abstract: We compared the long-term effects of generating questions by learners with answering questions (i.e., testing) and restudying in the context of a university lecture. In contrast to previous studies, students were not prepared for the learning strategies, learning content was experimentally controlled, and effects on factual and transfer knowledge were examined. Students' overall recall performance after one week profited from generating questions and testing but not from restudying. When analyzing the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
1
15
1
Order By: Relevance
“…Although self-testing impaired factual final test performance, we found no evidence that self-testing significantly affected performance on conceptual questions, positively or negatively. This is consistent with prior research that has shown little to no benefit of retrieval practice (Pan & Rickard, 2018), pretesting (Hausman & Rhodes, 2018), and self-testing (Bugg & McDaniel, 2012;Denner & Rickards, 1987; but see Ebersbach et al, 2020) for test questions that require inferences. Given the practical importance of learning more than facts, future research should identify ways to modify retrieval practice with provided or self-generated questions to enhance conceptual understanding (e.g., Nguyen & McDaniel, 2016).…”
Section: Type Of Final Test Questionsupporting
confidence: 89%
“…Although self-testing impaired factual final test performance, we found no evidence that self-testing significantly affected performance on conceptual questions, positively or negatively. This is consistent with prior research that has shown little to no benefit of retrieval practice (Pan & Rickard, 2018), pretesting (Hausman & Rhodes, 2018), and self-testing (Bugg & McDaniel, 2012;Denner & Rickards, 1987; but see Ebersbach et al, 2020) for test questions that require inferences. Given the practical importance of learning more than facts, future research should identify ways to modify retrieval practice with provided or self-generated questions to enhance conceptual understanding (e.g., Nguyen & McDaniel, 2016).…”
Section: Type Of Final Test Questionsupporting
confidence: 89%
“…The literature on question generation, in which learners devise practice questions after viewing a text or lecture, illustrates potential limits on the pedagogical benefits of creating content. In several studies, generating questions has yielded test performance that is better than a restudy condition but not a retrieval practice-only condition (e.g., Ebersbach et al, 2020;Weinstein et al, 2010; see also Hoogerheide et al, 2019). Potential explanations include the more time-consuming nature of generating questions, reduced learning efficiency, processing of extraneous information, and the need for specialized training beforehand (for discussions see Bae et al, 2019;Bugg & McDaniel, 2012;Davey & Bride, 1986).…”
Section: Does Generating Flashcard Content Elicit Productive Learning...mentioning
confidence: 99%
“…So, when this is the result of deliberate control (e.g., with an objective to create a resource) it leads to an interaction between existing knowledge and creative thinking which has a positive impact on memory (Ashby et al, 2002). This would suggest that creativity is a worthwhile metacognitive strategy for learning compared with popular activities, such as re‐reading over old notes (Ebersbatch et al, 2020). In clinical neuroanatomy education, student partners at Southampton have profited from the creative procedure through the process of active learning, which mirrors the active processes of drawing within a live lecture (Pickering, 2015).…”
Section: Descriptionmentioning
confidence: 99%
“…Additionally, their creative activities extend to generating questions for multimedia quizzes, case‐based scenarios, and clinical problem solving. There is evidence in favor of this type of engagement being superior for learning when compared to knowledge testing because it enhances both factual recall and transfer knowledge (Ebersbatch et al, 2020).…”
Section: Descriptionmentioning
confidence: 99%